Laser‐Induced Phase Transition and Patterning of hBN‐Encapsulated MoTe2. Issue 17 (24th January 2023) - Ryu, Huije; Lee, Yunah; Jeong, Jae Hwan; Lee, Yangjin; Cheon, Yeryun; Watanabe, Kenji; Taniguchi, Takashi; Kim, Kwanpyo; Cheong, Hyeonsik; Lee, Chul‐Ho; Lee, Gwan‐Hyoung
Abstract: Transition metal dichalcogenides exhibit phase transitions through atomic migration when triggered by various stimuli, such as strain, doping, and annealing. However, since atomically thin 2D materials are easily damaged and evaporated from these strategies, studies on the crystal structure and composition of transformed 2D phases are limited. Here, the phase and composition change behavior of laser‐irradiated molybdenum ditelluride (MoTe2 ) in various stacked geometry are investigated, and the stable laser‐induced phase patterning in hexagonal boron nitride (hBN)‐encapsulated MoTe2 is demonstrated. When air‐exposed or single‐side passivated 2H‐MoTe2 are irradiated by a laser, MoTe2 is transformed into Te or Mo3 Te4 due to the highly accumulated heat and atomic evaporation. Conversely, hBN‐encapsulated 2H‐MoTe2 transformed into a 1T′ phase without evaporation or structural degradation, enabling stable phase transitions in desired regions. The laser‐induced phase transition shows layer number dependence; thinner MoTe2 has a higher phase transition temperature. From the stable phase patterning method, the low contact resistivity of 1.13 kΩ µm in 2H‐MoTe2 field‐effect transistors with 1T′ contacts from the seamless heterophase junction geometry is achieved. This study paves an effective way to fabricate monolithic 2D electronic devices with laterally stitched phases and provides insights into phase and compositional changes in 2D materials. Abstract : By hBN‐encapsulation, the focused laser induces highly stable and reliable phase transition and patterning of thin MoTe2 . Various phases of 1T′, Mo3 Te4, and Te can be produced by laser irradiation, depending on the evaporation and temperature of the MoTe2 . The phase patterned 2H‐1T′ heterophase junction shows low contact resistivity of 1.13 kΩ µm.